The influence of additives in the stoichiometry of hybrid lead halide perovskites - Burgués-Ceballos, Ignasi; Savva, Achilleas; Georgiou, Efthymios; Kapnisis, Konstantinos; Papagiorgis, Paris; Mousikou, Androniki; Itskos, Grigorios; Othonos, Andreas S.; Choulis, Stelios A. (My University, 2017)
We investigate the employment of carefully selected solvent additives in the processing of a commercial perovskite precursor ink and analyze their impact on the performance of organometal trihalide perovskite (CH3NH3PbI3-xClx) photovoltaic devices. We provide evidence that the use of benzaldehyde can be used as an effective method to preserve the stoichiometry of the perovskite precursors in solution. Benzaldehyde based additive engineering shows to improve perovskite solid state film morphology and device performance of CH3NH3PbI3-xClx based solar cells.
Keywords: Additives; Cell engineering; Perovskite; Solar cells; Perovskite solar cells; Halide perovskites; Perovskite solids